Influence of separation properties and processing strategies on product characteristics in continuous fluidized bed spray granulation - Mueller, Daniel; Bück, Andreas; Tsotsas, Evangelos (Powder Technology, 2019)
The realization of continuous operation in fluidized bed spray granulation raises issues of process stability and product specification. It requires an appropriate process control strategy and a suitable granulator design. In previous work, a two-zone population balance (PB) model was developed and simulated product size distributions were evaluated by experiments in a Wurster granulator with external straight-duct air classification, however only regarding the process stability. The present contribution extends this population balance model with further equations for the purpose of product size control whereby the parameter setting of the former investigation serves as basis of the shown simulation study. Three process control strategies have been developed, implemented into the PB-model and investigated for diverse desired particle growth ratios and various separation sharpnesses. The simulation results show that only one of these strategies is able to provide the targeted requirements of both, process stability and product specification, but only for sufficiently good separation performance.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Continuous spray granulation; Fluidized bed; Population balances; Process control; Simulation; Straight-duct air classification; Wurster equipment